Kto jest „autorem" The Dark Side Of The Moon? O nadawcy rockowym - Rychlewski, Marcin (Przestrzenie Teorii, 2007)
The essay deals with the status of the sender in rock music. The rock music sender is invariably a collective entity (the musicians, the producer, the lyricist, the cover sleeve designer). A work of art in rock music (a song, an album) is always the sum total of various creative personalities as well as the end result of numerous compromises. In effect, it is often difficult to pinpoint a single intention behind a given message, which is why interpretations of such a message should disregard any commentary from the artists in question. The author draws an analogy between the rock music sender and the subject of literary creativity. Another characteristic of the rock music sender consists in their being both the "author" and the "performer" of the works within their repertoire (inasmuch as rock music cancels the oppositon: score/performance).